Can Cost-effective Reallocation of Inputs Increase the Efficiency of the Public Health System in Pakistan? (The Pakistan Development Review, 1997)
Heavy investment in many developing countries in the social sector including health is based on the premise that human capital is vital to the growth and development of a nation. However, Pakistan's spending on this sector has been one of the lowest in the region. In the present environment of high budget deficits, one does not expect substantial public funds to be forthcoming and diverted towards the social sector in the intermediate- or medium-term future. The critical issue facing the public sector should then be to design health policies which must be cost-effective and efficient. This study examines these health policy issues within the context of an optimisation framework for public health system, forecasts future upto (2002-03) and discusses an efficient optimal mix of health inputs, outputs, expenditures, and wage policies under alternative scenarios. The study recommends that, first, growth of health infrastructure building in the urban areas be slowed down in the short-term (two to three years), and some of the resources reallocated towards the rural sector either in terms of building new Basic Health Units or upgrading the existing Rural Health Centres. Second, not only attractive wage policies be formulated for health personnel, but the status of nurses in the public health system be also elevated by giving them higher grades. Third, for every rupee of development expenditure incurred, Public Health Department must plan or keep provisions for recurring outlays. All this reallocation of resources is feasible within the projected actual budget and it will lead to efficiency gains in the order of 8 to 10 percent for the entire public health system.